Effects of artificial light in indoor vertical garden on growth of Philodendron Lemon Lime and Philodendron Brasil - Phonpho, S.; Seesanong, S.; Yoosukyingsataporn, S. (International Journal of Agricultural Technology, 2021)
The effects in two types of light-emitting-diode (LED) lighting in a vertical garden on the growth of Philodendron Lemon Lime and Philodendron Brasil were investigatded. Result showed that the dependent variables of plant height, stem fresh weight, leaf area, leaf area index number leaf, total dry weight, chlorophyll a, chlorophyll b, chlorophyll a+b, carotenoids, spad, and shoot/root ratio. The most fundamental results revealed to be able to verify or reject prior agricultural theories for the full spectrum LEDs which better light sources than fluorescence LEDs. At 120 days after planting, full-spectrum LED lamps provided 94.56% which higher growth of Philodendron Lemon Lime, Philodendron Brasil than fluorescent LED lamps. It is proved that a vertical garden and the beauty of the vertical garden showing the best growth on the leaf shapes and colorful leaf of Philodendron Lemon Lime under full-spectrum lamps. Other specific findings may benefit for future investigation of philodendrons and other plants